A study on the mouldability of POM microdetails in moulding blocks using micromanufacturing technologies - Vasco, Joel Oliveira Correia (2010)
The integration of micro fabrication and micro-moulding techniques contributed to the massifica-tion of microsystems in several domains of activity at feasible costs. In this study the mouldability of microdetails generated by microEDM, micromilling and laser milling in microinjection moulding blocks is assessed. For that purpose, a polyacetal for precision microparts is used to evaluate how mi-crofeatures are replicated in microinjection mould-ing. The mouldings were produced in a instru-mented micromould with two interchangeable moulding blocks, enabling the test of various mould inserts. The processing conditions were simulated with the Moldex3D commercial software. Despite the commercial success of microinjection moulding, the process involves microscale phe-nomena that make the polymer flow different from the conventional flow at the macro scale. The mi-croinjection tests and the simulation allowed the gathering of knowledge to incorporate on mathe-matical models and simulation software, enabling the filling simulations at this scale being more ac-curate. Further to the assessment of the microde-tails mouldability, the surface replication and finish-ing of the mouldings were analysed by optical and SEM microscopy.